Growth rates of preschool children in Bursa, Turkey - Köksal, Orhan; Yılmazsoy, Hayrettin (The Turkish Journal of Pediatrics, 1961)
A partly longitudinal growth study of 416 Turkish infants was carried out. This study was based on the records of the Bursa (Turkey) Merinos Textile Factory Crèche.The mean values, with standard errors and standard deviations, of the weight and height of Turkish boys and girls are shown in the tables.The Turkish figures are compared with those from the U. K. and Mexico.The authors are indebted to Dr. Turhan Akbulut, the chief medical officer of the Merinos Factory, for permission to analyze the records and to Güngör Akmenek and Bayan Sabahat for their kind help.